A methodology for improving wind energy production in low wind speed regions, with a case study application in Iraq. (January 2019) - Darwish, Abdul Salam; Shaaban, Sabry; Marsillac, Erika; Mahmood, Nazar Muneam
Highlights: Addresses wind turbine optimization in low wind speed areas. Provides a comprehensive, iterative implementation methodology. Provides strategic guidance for selection, matching, layout and installation. Illustrates value via a case study application in Iraq. Abstract: Wind is one of the most promising sources of alternative, renewable energy, particularly for developing economies. Wind turbines have been routinely used for electrical power generation since the late 19th century, but growing concerns over the price and environmental impacts of fossil fuels have spurred rapid industry growth. In addition, renewable energy resources are of keen, contemporary interest due to rising global energy demands. To contribute to the body of knowledge on optimizing wind energy production, this paper introduces a comprehensive, iterative methodology for selecting, matching, laying out and installing the most suitable wind turbine system for low wind speed regions, with the objective of generating improved annual energy power. The methodology is useful for the strategic planning and implementation of wind power stations. Iraq was selected as a case study example of implementation in a low wind speed country with vast open flat terrain.